2014
DOI: 10.12988/ams.2014.45389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four methods for estimating the Weibull distribution parameters

Abstract: In this paper we study the performance of the least square method, the weighted least square method, the maximum likelihood method and the method of moments for estimating the Weibull distribution parameters. The comparison is based on the Monte Carlo simulation, the methods are compared in terms of the root mean square error and sample size n. The comparison shows that the maximum likelihood method and the method of moments provide similar estimates. We recommend the maximum likelihood method to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 9 publications
1
20
1
2
Order By: Relevance
“…It follows that the average WPD associated with the PDF of the wind speed random variable is given as Observe also that the average WPD given by (40) is obtained by computing the third moment about zero of the wind speed random variable . If follows the Weibull distribution, one readily obtain the WPD using (24) as The cube of the mean wind speed for a wind speed random variable following the Weibull distribution is given by It follows that the EPF for a wind speed random variable following the Weibull is given by Equating the population moments which make up (43) to their corresponding sample moments we obtain…”
Section: Energy Pattern Factor Methods (Epfm)mentioning
confidence: 99%
“…It follows that the average WPD associated with the PDF of the wind speed random variable is given as Observe also that the average WPD given by (40) is obtained by computing the third moment about zero of the wind speed random variable . If follows the Weibull distribution, one readily obtain the WPD using (24) as The cube of the mean wind speed for a wind speed random variable following the Weibull distribution is given by It follows that the EPF for a wind speed random variable following the Weibull is given by Equating the population moments which make up (43) to their corresponding sample moments we obtain…”
Section: Energy Pattern Factor Methods (Epfm)mentioning
confidence: 99%
“…Pobočíková & Sedliačková [12] have compared four methods for parameters estimation of Weibull distribution namely least squares, weighted least squares, maximum likelihood and method of moments. The numerical results indicated that the method of moments and maximum likelihood provide equivalent results but they recommended maximum likelihood because of its optimal properties.…”
Section: Maximum Likelihood Estimation Is Considered As Most Importanmentioning
confidence: 99%
“…is the Euler's Gamma function. To estimate the parameters , k λ , exists various methods like the mean squared method or the moment method [16].…”
Section: Marginals Under Studymentioning
confidence: 99%